2016
DOI: 10.1097/md.0000000000004856
|View full text |Cite|
|
Sign up to set email alerts
|

Inspiratory muscle training in stroke patients with congestive heart failure

Abstract: BackgroundCardiopulmonary function can be adversely affected after a cerebrovascular accident in patients with congestive heart failure (CHF). The aim of this study was to investigate the efficacy and feasibility of inspiratory muscle training (IMT) for stroke patients with CHF.MethodsA prospective randomized single-blind controlled trial was conducted in a single tertiary medical center in southern Taiwan between May 2011 and July 2015. Forty-one patients were enrolled, of whom 21 completed the study (IMT gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…Of these, 754 were excluded by irrelevancy and 46 were full-text revised. Finally, nineteen studies aimed to assess the effectiveness of RMT on pulmonary function and functional capacity variables in patients with stroke were included in the meta-analysis [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Figure 1 shows the flow of study selection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 754 were excluded by irrelevancy and 46 were full-text revised. Finally, nineteen studies aimed to assess the effectiveness of RMT on pulmonary function and functional capacity variables in patients with stroke were included in the meta-analysis [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Figure 1 shows the flow of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 depicts the characteristics of the included studies and the participants. Studies were conducted in Korea [20,[22][23][24][25][26][27]33,34,36], Turkey, Spain [28,30], Brazil [21,35], Germany [32], United Kingdom [31] and Taiwan [19,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired respiratory fucntion may be a consequence of weakness of the respiratory muscles and postural trunk dysfunction. Several studies consistently reported highter positioning of the paretic hemidiaphragm associated with decreases in diaphragmatic excursion during spontaneous breathing and hyperventilation 3 ) . Previous studies 1 , 2 , 3 ) suggested that inspiratory muscle are critical factor to solve this problems.…”
Section: Introductionmentioning
confidence: 97%
“…In the article “Inspiratory muscle training in stroke patients with congestive heart failure: A CONSORT-compliant prospective randomized single-blind controlled trial”, [ 1 ] which appeared in Volume 95, Issue 37 of Medicine , a footnote should have been included noting that Mei-Yun Liaw is the co-first author of the article.…”
mentioning
confidence: 99%